Elevated DNA damage response in pancreatic cancer - Osterman, Michael (Histochem Cell Biol, 2014)
Pancreatic cancer is one of the most aggressive and intractable human malignant tumors and a leading cause of cancer-related deaths across the world, with incidence equaling mortality. Because of the extremely high malignance, this disease is usually diagnosed at its advanced stage and recurs even after surgical excision. Pancreatic adenocarcinoma is generally thought to arise from pathological changes of pancreatic duct, and the pancreatic ductal adenocarcinoma (PDA) accounts for more than 90% of malignant neoplasms of the pancreas. To date, scientists have revealed several risk factors for pancreatic cancer, including smoking, family history, and ageing. However, the underlying molecular mechanism remains unclear. Meanwhile, more mutations of DNA damage response factors have been identified in familial pancreatic cancers, implying a potential link between DNA damage and pancreatic cancer. DNA damage is a recurring phenomenon in our bodies which could be induced by exogenous agents and endogenous metabolism. Accumulated DNA lesions cause genomic instability which eventually results in tumorigenesis. In this study, we showed obvious DNA damages existed in human pancreatic cancer, which activated DNA damage response and the DNA repair pathway including ATM, DNA-PK, CHK1 and CHK2. The persistent DNA damage in pancreatic tissue may be the source for its tumorigenesis.